2015
DOI: 10.1103/physrevd.91.084004
|View full text |Cite
|
Sign up to set email alerts
|

Einstein-Gauss-Bonnet traversable wormholes satisfying the weak energy condition

Abstract: In this paper, we explore higher-dimensional asymptotically flat wormhole geometries in the framework of Gauss-Bonnet (GB) gravity and investigate the effects of the GB term, by considering a specific radial-dependent redshift function and by imposing a particular equation of state. This work is motivated by previous assumptions that wormhole solutions were not possible for the k = 1 and α < 0 case, where k is the sectional curvature of an (n − 2)-dimensional maximally symmetric space, and α is the Gauss-Bonne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(119 citation statements)
references
References 72 publications
4
115
0
Order By: Relevance
“…Our results are consistent with the work already available in the literature [55,56]. Our results are also similar to that obtained in simple f (R) gravity [35] (that is, the case λ = 0).…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with the work already available in the literature [55,56]. Our results are also similar to that obtained in simple f (R) gravity [35] (that is, the case λ = 0).…”
Section: Discussionsupporting
confidence: 82%
“…In f (G, T ) gravity, we find that massive test particles follow the non-geodesic trajectories due to the presence of an extra force [4]. The above inequalities (14) with T eff αβ provide the null, weak, strong (SEC) and dominant (DEC) energy conditions as…”
Section: Field Equations For Wormhole Constructionmentioning
confidence: 99%
“…Sharif and Rani [13] studied static spherically symmetric WH solutions for exponential as well as logarithmic forms of generalized teleparallel gravity and found that WEC is violated in galactic halo region for both models. Mehdizadeh et al [14] discussed realistic traversable WH solutions in Einstein GB gravity. We have explored WH geometries for traceless, isotropic as well as barotropic matter distributions and concluded that realistic WH solutions exist in f (G) gravity only for radial barotropic fluid [15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a plethora of wormhole solutions beyond GR have been found in a variety of theories, such as in conformal Weyl gravity [58], Kaluza–Klein [5961], Brans–Dicke [6265], Gauss–Bonnet [6669], Lovelock [70, 71] braneworlds [62, 7274], Hor̆ava–Lifshitz [75, 76], Eddington-inspired Born–Infeld [7779], metric [8083] and Palatini [84, 85] approaches of f ( R ) gravity and extensions [8688], the modified teleparalellism framework [89, 90] or Einstein–Cartan theory [91]. …”
Section: Introductionmentioning
confidence: 99%